Burundi : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Burundi. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Burundi's economy has shown resilience to the COVID-19 and Ukraine war shocks. Prior to the pandemic, the economy was recovering from the political and security crisis that followed late President Nkurunziza's decision to run for a third term in 2015, with growth close to 2 percent in 2019. Difficult macroeconomic policy challenges persisted, nevertheless. The pandemic has taken a toll on the post-conflict fragile country, but COVID-19 contagion remained fairly contained and growth was positive. The war in Ukraine is compounding the adverse effects of the pandemic, with deteriorating terms of trade and the resulting domestic inflation threatening already-challenging living standards. Sanctions from the U.S. and E.U.-legacy of the 2015 crisis-have now been lifted. The U.N. Security Council ended mandatory reporting in Burundi and the country has reengaged with the international community. The 2022 Article IV consultation seals the full reengagement with the IMF-the last one was concluded in 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Burundi